Detection of 135Cs by accelerator mass spectrometry. (15th January 2015) - MacDonald, C.; Charles, C. R. J.; Cornett, R. J.; Zhao, X. L.; Kieser, W. E.; Litherland, A. E.
<x xml:space="preserve">Abstract</x> RATIONALE The ability to measure both 135Cs and 137Cs can provide an estimate of the age and source of Cs isotopes in an environmental sample. Accelerator mass spectrometry (AMS) consistently reports lower abundance sensitivities than other techniques and, with the addition of an on‐line reaction cell, simpler isobaric suppression. Therefore, an AMS methodology was developed to measure Cs isotopes using Cs<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbqbnw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />F2−</alternatives> as the initial anion. METHODS The ion beam is passed through the Isobar Separator for Anions (ISA) where it is captured by radiofrequency quadrupoles in a gas cell before injection into the tandem accelerator. In the ISA, the beam reacts with O2 gas, selectively removing the Ba<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbqbq0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />F2−</alternatives> and leaving the Cs analyte to be reaccelerated and sent through the remainder of the AMS system. RESULTS The Ba<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbqbs3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />F2−</alternatives> signal was attenuated by a factor of 105 in the ISA while 25% of the original Cs<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbqc5p" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />F2−</alternatives> current was transmitted into the accelerator. 135Cs was measured without any interference from 133Cs to an abundance sensitivity of 1.3 × 10–10. The abundances of four stable Ba isotopes (masses 133, 134, 135 and 137) were measured and no isotope‐dependent bias was detected using the ISA in vacuum. CONCLUSIONS The results demonstrate the feasibility of measuring long‐lived Cs isotopes without Ba interference by AMS with on‐line isobar separation and the ability to use shorter lived Cs isotopes for yield tracing. Copyright © 2014 John Wiley & Sons, Ltd.